3D cloud masking across a broad swath using multi-angle polarimetry and deep learning - S. R. Foley; S. R. Foley; K. D. Knobelspiesse; A. M. Sayer; A. M. Sayer; M. Gao; M. Gao; J. Hays; J. Hoffman (Atmospheric Measurement Techniques)
Understanding the 3D structure of clouds is of crucial importance to modeling our changing climate. Both active and passive sensors are restricted to two dimensions: as a cross-section in the active case and an image in the passive case. However, multi-angle sensor configurations contain implicit information about 3D structure, due to parallax and atmospheric path differences. Extracting that implicit information requires computationally expensive radiative transfer techniques. Machine learning, as an alternative, may be able to capture some of the complexity of a full 3D radiative transfer solution with significantly less computational expense. In this work, we develop a machine-learning model that predicts radar-based vertical cloud profiles from multi-angle polarimetric imagery. Notably, these models are trained only on center swath labels but can predict cloud profiles over the entire passive imagery swath. We compare with strong baselines and leverage the information–theoretic nature of machine learning to draw conclusions about the relative utility of various sensor configurations, including spectral channels, viewing angles, and polarimetry. Our experiments show that multi-angle sensors can recover surprisingly accurate vertical cloud profiles, with the skill strongly related to the number of viewing angles and spectral channels, with more angles yielding high performance, and with the oxygen A band strongly influencing skill. A relatively simple convolutional neural network shows nearly identical performance to the much more complicated U-Net architecture. The model also demonstrates relatively lower skill for multilayer clouds, horizontally small clouds, and low-altitude clouds over land, while being surprisingly accurate for tall cloud systems. These findings have promising implications for the utility of multi-angle sensors on Earth-observing systems, such as NASA's Plankton, Aerosol, Cloud, ocean Ecosystem (PACE) and Atmosphere Observing System (AOS), and encourage future applications of computer vision to atmospheric remote sensing.